2022
DOI: 10.2147/dddt.s384607
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Study of Shaoyao Plants Decoction on the Proximal and Distal Colon in Mice with Dextran Sulfate Sodium-Induced Colitis by UPLC-Q-TOF-MS

Abstract: Shaoyao decoction (SYD) is a traditional Chinese medicine used to treat ulcerative colitis (UC). The exact mechanism of action of SYD in UC treatment is still unclear. Here, we examined the therapeutic effects of SYD in mice with dextran sulfate sodium (DSS)-induced colitis and explored the underlying mechanism. Methods: The experimental group was divided into normal control, UC, and SYD treatment groups. The UC model of C57BL/6 mice was induced using 3% (w/v) DSS for 7 days. SYD was orally administered for 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Previous studies indicated that plasma metabolite disorders were present in the development of UC. 27 Consequently, changes in plasma metabolic profiles might reveal the potential mechanism of 6-G to ameliorate UC. This study identified 19 metabolites that could be notably regulated by 6-G, mainly involving LA metabolism, AA metabolism, glycerophospholipid metabolism, unsaturated fatty acid biosynthesis, ALA metabolism, and primary bile acid biosynthesis.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that plasma metabolite disorders were present in the development of UC. 27 Consequently, changes in plasma metabolic profiles might reveal the potential mechanism of 6-G to ameliorate UC. This study identified 19 metabolites that could be notably regulated by 6-G, mainly involving LA metabolism, AA metabolism, glycerophospholipid metabolism, unsaturated fatty acid biosynthesis, ALA metabolism, and primary bile acid biosynthesis.…”
Section: Papermentioning
confidence: 99%
“…33 LysoPE was demonstrated to reduce inflammation, mucosal damage, and intestinal permeability in UC mice. 27 In particular, it was reported that PC levels were decreased in UC patients because PC could be cleaved by secretory PLA2 to inflammatory AA. 31 Besides, PE was also a precursor for generating GpAEA, which could be hydrolyzed to AA.…”
Section: Papermentioning
confidence: 99%
“…It comprises baicalensis , coptis , paeonia lactiflora , angelica , aucklandiae radix , areca , rhubarb , cinnamon and liquorice . Some of these herbs have been scientifically shown to mitigate local intestinal inflammation in UC through the regulation of signaling pathways involving nuclear factor kappa-B (NF-κB), notch and Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3), while also affecting the intestinal flora and its metabolites [ 4 , 5 ]. For example, paeoniflorin and baicalin, active constituents identified in SYD through reverse phase high-performance liquid chromatography analysis [ 6 ], have been found to possess anti-inflammatory properties by primarily inhibiting the activation of the NF-κB signaling pathway and influencing the composition of the intestinal flora [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%